A Review of Embodiment in Autism Spectrum Disorders - Eigsti, Inge-Marie (Frontiers in Psychology, 2013)
In classical approaches to cognition, sensory, motor and emotional experiences are stripped of domain-specific perceptual and sensorimotor information, and represented in a relatively abstract form. In contrast, the embodied cognition framework suggests that our representations retain the initial imprint of the manner in which information was acquired. In this paper, we argue that individuals with ASD display impairments in the temporal coordination of motor and conceptual information (as shown in gesture research) and striking deficits in the interpersonal mimicry of motor behaviors (as shown in yawning research) – findings we believe are consistent with an embodied account of ASD that includes, but goes beyond, social experiences and is driven in part by significant but subtle motor deficits. In this paper, we review the research examining an embodied cognition account of ASD, and discuss its implications.